Method for preparing high-efficiency carbon-based hole-free perovskite solar cell

By using octyl ammonium acetate as a passivator to reduce the surface defect density of the perovskite layer and improve interface contact, the problem of low efficiency of carbon-based hole-free perovskite solar cells is solved, and efficiency and stability are improved.

CN119816168APending Publication Date: 2025-04-11NINGBO INST OF NORTHWESTERN POLYTECHNICAL UNIV

Patent Information

Application Number
CN202510019307.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing carbon-based hole-free perovskite solar cells have problems such as poor interface contact between the perovskite layer and the carbon electrode, many defects in the absorbing layer, and high non-radiation recombination rate, resulting in low efficiency.

Method used

By using octylammonium acetate as a passivator, the surface defect density of the perovskite layer is reduced, and the stability of the solar cell is improved by the hydrophobicity of its octane chain. The specific steps include cleaning the glass substrate, spin coating the electron transport layer, configuring the calcium carbonate precursor solution, coating and annealing the perovskite layer, configuring the passivator solution, spin coating the passivation layer, and brushing the carbon slurry on the passivation layer to prepare the carbon electrode.

Benefits of technology

It effectively reduces the surface defect density of the perovskite layer, improves the interface contact between the perovskite layer and the carbon electrode, and improves the efficiency and stability of solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119816168A_ABST
    Figure CN119816168A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a high-efficiency carbon-based hole-free perovskite solar cell. The method comprises the following steps: cleaning a glass substrate; spin-coating an electron transport layer on the glass substrate; preparing a perovskite precursor solution, uniformly coating the prepared perovskite precursor solution on the surface of the electron transport layer to obtain a perovskite wet film, and annealing the perovskite wet film to obtain a perovskite layer; preparing a passivator solution, and spin-coating a passivation layer on the surface of the perovskite layer; and brushing carbon paste on the passivation layer and annealing to obtain the carbon electrode perovskite solar cell. According to the invention, the surface defect density of the perovskite layer can be reduced, the interface contact condition between the perovskite layer and the carbon electrode can be improved, and the octalkyl chain contained in the octyl ammonium acetate has hydrophobicity, so that the stability of the carbon-based perovskite solar cell can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of solar cells, and in particular to a method for preparing a high-efficiency carbon-based hole-free perovskite solar cell. Background Art

[0002] As a major way to utilize solar energy, solar cells can convert light energy into electrical energy. Currently, researchers have developed various types of solar cells. Among them, perovskite solar cells have become a research hotspot in recent years due to their strong photoelectric conversion ability, adjustable band gap, and simple manufacturing process. Since 2009, the efficiency of perovskite solar cells has increased from 3.8% to 26%, which can be regarded as a new hope in the photovoltaic field.

[0003] Compared with the traditional structure of perovskite solar cells, carbon-based perovskite solar cells without hole transport layer have simple process, low cost, good stability, do not require expensive hole transport layer materials and precious metal electrodes, and have greater development potential. However, this structure is currently mostly prepared in a glove box, which has extremely high requirements for humidity, temperature and other environmental conditions, greatly increasing the cost and difficulty of industrial preparation of high-efficiency carbon-based perovskite solar cells without hole transport layer. At the same time, this structure also has some interface problems, such as poor interface contact between the perovskite layer and the carbon electrode, many defects in the light absorption layer, high non-radiative recombination rate, and low efficiency. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing a high-efficiency carbon-based hole-free perovskite solar cell.

[0005] The innovation of the present invention lies in that the method of the present invention can reduce the surface defect density of the perovskite layer, improve the interface contact between the perovskite layer and the carbon electrode, and the octaalkyl chain contained in octyl ammonium acetate is hydrophobic, which can improve the stability of the carbon-based perovskite solar cell.

[0006] In order to achieve the above-mentioned object of the invention, the technical solution of the present invention is:

[0007] A method for preparing a high-efficiency carbon-based hole-free perovskite solar cell comprises the following steps:

[0008] (1) Cleaning the glass substrate;

[0009] (2) spin coating an electron transport layer on a glass substrate;

[0010] (3) preparing a perovskite precursor solution, uniformly coating the prepared perovskite precursor solution on the surface of the electron transport layer to obtain a perovskite wet film, and annealing the perovskite wet film to obtain a perovskite layer;

[0011] (4) preparing a passivation agent solution, and spin coating a passivation layer on the surface of the perovskite layer. The passivation agent solution is prepared by dissolving octyl ammonium acetate in isopropanol and stirring evenly. The concentration of the passivation agent solution is 0.01 to 0.03 M.

[0012] (5) Brushing carbon paste on the passivation layer and annealing to obtain a carbon electrode perovskite solar cell.

[0013] Furthermore, when cleaning the glass substrate, anhydrous ethanol, daily detergent, deionized water, isopropanol and anhydrous ethanol are used to ultrasonically clean the glass substrate for 15 to 20 minutes respectively, and then heated at 50 to 60°C.

[0014] Dry under low temperature for 10 to 15 minutes, and then treat with ultraviolet ozone (UV) for 10 to 20 minutes.

[0015] Furthermore, in step (3), the perovskite wet film is coated by spin coating.

[0016] Furthermore, the calcium carbonate precursor solution is prepared by dissolving lead iodide and methylammonium iodide in an organic solvent and stirring the solution for 5 to 8 hours. The molar concentration of lead iodide is 2 to 2.3 mol / L, and the molar concentration of methylammonium iodide is 2 to 2.3 mol / L. The organic solvent is a mixed solvent of dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) in a volume ratio of 4:1 to 9:1.

[0017] Furthermore, every 1.2×1.2cm 2 40-60 μL of passivation agent solution is coated on the perovskite layer, and the coating machine is started. The spin coating speed is 4000 rpm and the spin coating time is 30 s. After the spin coating is completed, the passivation layer is obtained by heating at 100° C. for 5-10 min.

[0018] Furthermore, the spin-coated electron transport layer is prepared by mixing a 15 wt % tin dioxide aqueous dispersion and deionized water in a volume ratio of 1:4 to obtain a tin oxide solution, and applying the tin oxide solution by spin coating on each 1.2×1.2 cm 2 45ul of tin oxide solution was spin-coated on a glass substrate, and the coating machine was started. The coating speed was 4000 rpm and the coating time was 30s. After the coating was completed, the electron transport layer was heated at 150°C for 30min to obtain the electron transport layer.

[0019] Furthermore, the coated perovskite precursor solution is obtained by filtering the stirred perovskite precursor solution with a disposable sterile syringe with a polytetrafluoroethylene organic filter membrane, and then coating the solution evenly on the electron transport layer, with a thickness of 1×1 cm 240 μL of perovskite precursor solution was coated on the electron transport layer, and the coating machine was started. The spin coating speed was 3000 rpm and the spin coating time was 30 s. At the 15th s of spin coating, 300 μL of anti-solvent ethyl acetate was added.

[0020] Furthermore, in step (3), the perovskite wet film is annealed by heating at 130° C. for 10 to 15 minutes to obtain the perovskite layer.

[0021] Furthermore, the coating process and annealing process of the titanium ore layer are both carried out in an air environment with a humidity requirement of 40-50%.

[0022] Furthermore, in step (5), the carbon paste is a conductive carbon paste, and the conductive carbon paste is printed on the surface of the passivation layer using a screen printing method, and heated at 120° C. for 15 minutes to obtain a carbon electrode perovskite solar cell.

[0023] The beneficial effects of the present invention are:

[0024] 1. In the present invention, octyl ammonium acetate is used to passivate the surface of the perovskite layer. The carboxylic acid group can react with the cations on the surface of the perovskite layer through ionic bonds to passivate the surface positive charge defects. At the same time, the amino ions can passivate the negative charge defects on the surface of the perovskite layer through the action of ionic bonds and hydrogen bonds, thereby effectively reducing the surface defect density of the perovskite layer and improving the interface contact between the perovskite layer and the carbon electrode. The octaalkyl chain contained in octyl ammonium acetate is hydrophobic, which can improve the stability of the carbon-based perovskite solar cell. Through experimental tests, the efficiency and repeatability of the device after passivation agent optimization are improved.

[0025] 2. The method of the present invention can be prepared in air, with simple process, low cost and good stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The results of scanning electron microscopy are shown in FIG. 1 , with Comparative Example 1 on the left and Example 3 on the right. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings.

[0028] Example 1: A method for preparing a high-efficiency carbon-based hole-free perovskite solar cell, comprising the following steps:

[0029] (1) Cleaning the glass substrate: using anhydrous ethanol, daily detergent, deionized water, isopropyl alcohol and anhydrous ethanol to ultrasonically clean the glass substrate for 15 minutes, drying it at 50°C for 10 minutes, and then treating it with ultraviolet ozone (UV).

[0030] 10min;

[0031] (2) Spin coating an electron transport layer on a glass substrate. The spin coating electron transport layer is prepared by mixing a 15 wt % tin dioxide aqueous dispersion and deionized water in a volume ratio of 1:4 to obtain a tin oxide solution. The tin oxide solution is applied by spin coating on each 1.2×1.2 cm 2 45ul of tin oxide solution was spin-coated on a glass substrate, and a coating machine was started. The coating speed was 4000 rpm and the coating time was 30s. After the coating was completed, the electron transport layer was heated at 150°C for 30min to obtain a electron transport layer.

[0032] (3) A perovskite precursor solution is prepared, and the prepared perovskite precursor solution is evenly coated on the surface of the electron transport layer to obtain a perovskite wet film. The perovskite wet film is coated by spin coating, and the perovskite wet film is annealed to obtain a perovskite layer. The perovskite precursor solution is prepared by dissolving lead iodide and methylammonium iodide in an organic solvent and stirring for 5 hours. The molar concentration of lead iodide is 2 mol / L, and the molar concentration of methylammonium iodide is 2 mol / L. The organic solvent is a mixed solvent of dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) in a volume ratio of 4:1. The coated perovskite precursor solution is prepared by filtering the stirred perovskite precursor solution with a disposable sterile syringe with a polytetrafluoroethylene organic filter membrane, and then evenly coating it on the electron transport layer, with a surface area of ​​1×1 cm 2 40 μL of perovskite precursor solution was coated on the electron transport layer, and the coating machine was started. The spin coating speed was 3000 rpm and the spin coating time was 30 s. 300 μL of anti-solvent ethyl acetate was added at the 15th s of spin coating. The perovskite wet film was annealed by heating at 130°C for 10 min to obtain the perovskite layer. The coating and annealing processes of the titanium layer were carried out in an air environment with a humidity requirement of 40%.

[0034] (4) Prepare a passivation solution and spin-coat the passivation layer on the surface of the perovskite layer. The passivation solution is prepared by dissolving octyl ammonium acetate in isopropanol and stirring evenly. The concentration of the passivation solution is 0.01 M. 2 40 μL of the passivation agent solution was coated on the perovskite layer, and the coating machine was started. The spin coating speed was 4000 rpm and the spin coating time was 30 s. After the spin coating was completed, the passivation layer was heated at 100° C. for 5 min.

[0035] (5) Brushing carbon paste on the passivation layer and annealing to obtain a carbon electrode perovskite solar cell, wherein the carbon paste is a conductive carbon paste, and the conductive carbon paste is printed on the surface of the passivation layer by a screen printing method, and heated at 120° C. for 15 minutes to obtain a carbon electrode perovskite solar cell.

[0036] Example 2: A method for preparing a high-efficiency carbon-based hole-free perovskite solar cell, comprising the following steps:

[0037] (1) Cleaning the glass substrate: using anhydrous ethanol, daily detergent, deionized water, isopropyl alcohol and anhydrous ethanol to ultrasonically clean the glass substrate for 17 minutes, then drying it at 55°C for 12 minutes, and then using ultraviolet ozone (UV)

[0038] Process for 15 minutes;

[0039] (2) Spin coating an electron transport layer on a glass substrate. The spin coating electron transport layer is prepared by mixing a 15 wt % tin dioxide aqueous dispersion and deionized water in a volume ratio of 1:4 to obtain a tin oxide solution. The tin oxide solution is applied by spin coating on each 1.2×1.2 cm 2 45ul of tin oxide solution was spin-coated on a glass substrate, and a coating machine was started. The coating speed was 4000 rpm and the coating time was 30s. After the coating was completed, the electron transport layer was heated at 150°C for 30min to obtain a electron transport layer.

[0040] (3) preparing a perovskite precursor solution, and uniformly coating the prepared perovskite precursor solution on the surface of the electron transport layer to obtain a perovskite wet film. The perovskite wet film is coated by spin coating, and the perovskite wet film is annealed to obtain a perovskite layer. The perovskite precursor solution is prepared by dissolving lead iodide and methylammonium iodide in an organic solvent and stirring for 7 hours. The molar concentration of lead iodide is 2.1 mol / L, and the molar concentration of methylammonium iodide is 2.1

[0041] mol / L, the organic solvent is dimethylformamide (DMF) with a volume ratio of 6:1

[0042] The perovskite precursor solution is a mixed solvent of dimethyl sulfoxide (DMSO). The perovskite precursor solution is stirred evenly, filtered with a disposable sterile syringe with a polytetrafluoroethylene organic filter membrane, and then evenly coated on the electron transport layer, with a 1×1 cm 2 40 μL of perovskite precursor solution was coated on the electron transport layer, and the coating machine was started. The spin coating speed was 3000 rpm and the spin coating time was 30 s. 300 μL of anti-solvent ethyl acetate was added at the 15th s of spin coating. The perovskite wet film was annealed by heating at 130°C for 12 min to obtain the perovskite layer. The coating and annealing processes of the titanium layer were carried out in an air environment with a humidity requirement of 45%.

[0043] (4) Prepare a passivation solution and spin-coat the passivation layer on the surface of the perovskite layer. The passivation solution is prepared by dissolving octyl ammonium acetate in isopropanol and stirring evenly. The concentration of the passivation solution is 0.02 M. 2The perovskite layer is coated with 50

[0044] μL of passivation agent solution, start the coating machine, spin coating speed is 4000 rpm, spin coating time is 30s, after spin coating, heat at 100℃ for 7min to obtain the passivation layer;

[0045] (5) Brushing carbon paste on the passivation layer and annealing to obtain a carbon electrode perovskite solar cell, wherein the carbon paste is a conductive carbon paste, and the conductive carbon paste is printed on the surface of the passivation layer by a screen printing method, and heated at 120° C. for 15 minutes to obtain a carbon electrode perovskite solar cell.

[0046] Example 3: A method for preparing a high-efficiency carbon-based hole-free perovskite solar cell, comprising the following steps:

[0047] (1) Cleaning the glass substrate: when cleaning the glass substrate, use anhydrous ethanol, daily detergent, deionized water, isopropyl alcohol and anhydrous ethanol to ultrasonically clean the glass substrate for 20 minutes respectively, then dry it at 60°C for 15 minutes, and then use ultraviolet ozone (UV)

[0048] Process for 20 minutes;

[0049] (2) Spin coating an electron transport layer on a glass substrate. The spin coating electron transport layer is prepared by mixing a 15 wt % tin dioxide aqueous dispersion and deionized water in a volume ratio of 1:4 to obtain a tin oxide solution. The tin oxide solution is applied by spin coating on each 1.2×1.2 cm 2 45ul of tin oxide solution was spin-coated on a glass substrate, and a coating machine was started. The coating speed was 4000 rpm and the coating time was 30s. After the coating was completed, the electron transport layer was heated at 150°C for 30min to obtain a electron transport layer.

[0050] (3) preparing a perovskite precursor solution, and uniformly coating the prepared perovskite precursor solution on the surface of the electron transport layer to obtain a perovskite wet film. The perovskite wet film is coated by spin coating, and the perovskite wet film is annealed to obtain a perovskite layer. The perovskite precursor solution is prepared by dissolving lead iodide and methylammonium iodide in an organic solvent and stirring for 8 hours. The molar concentration of lead iodide is 2.3 mol / L, and the molar concentration of methylammonium iodide is 2.3

[0051] mol / L, the organic solvent is dimethylformamide (DMF) with a volume ratio of 9:1

[0052] The perovskite precursor solution is a mixed solvent of dimethyl sulfoxide (DMSO). The perovskite precursor solution is stirred evenly, filtered with a disposable sterile syringe with a polytetrafluoroethylene organic filter membrane, and then evenly coated on the electron transport layer, with a 1×1 cm 240 μL of perovskite precursor solution was coated on the electron transport layer, and the coating machine was started. The spin coating speed was 3000 rpm and the spin coating time was 30 s. 300 μL of anti-solvent ethyl acetate was added at the 15th s of spin coating. The perovskite wet film was annealed by heating at 130°C for 15 min to obtain the perovskite layer. The coating and annealing processes of the titanium layer were carried out in an air environment with a humidity requirement of 50%.

[0053] (4) Prepare a passivation solution and spin-coat the passivation layer on the surface of the perovskite layer. The passivation solution is prepared by dissolving octyl ammonium acetate in isopropanol and stirring evenly. The concentration of the passivation solution is 0.03 M. 2 The perovskite layer is coated with 60

[0054] μL of passivation agent solution, start the coating machine, spin coating speed is 4000 rpm, spin coating time is 30s, after spin coating, heat at 100℃ for 10min to obtain the passivation layer;

[0055] (5) Brushing carbon paste on the passivation layer and annealing to obtain a carbon electrode perovskite solar cell, wherein the carbon paste is a conductive carbon paste, and the conductive carbon paste is printed on the surface of the passivation layer by a screen printing method, and heated at 120° C. for 15 minutes to obtain a carbon electrode perovskite solar cell.

[0056] Comparative Example 1: Referring to Example 1, step (4) is eliminated, and in step (5), carbon slurry is brushed on the perovskite layer and annealed to obtain a carbon electrode perovskite solar cell.

[0057] The performance of the prepared carbon electrode perovskite solar cells is shown in Table 1

[0058] Table 1

[0059]

[0060] At the same time, by comparing Examples 1 to 3 with Comparative Example 1, it can be found that after the surface of the perovskite layer is passivated with octyl ammonium acetate, the open circuit voltage of the device is significantly improved, which indicates that the passivator reduces the defect density on the surface of the perovskite film, improves the interface contact between the perovskite layer and the carbon electrode, reduces the recombination of carriers, improves the carrier transport capacity, and improves the efficiency and stability of the solar cell.

[0061] The described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A method for preparing a high-efficiency carbon-based hole-free perovskite solar cell, characterized in that: The following steps are involved: (1) Cleaning glass substrate; (2) Spin coating an electron transport layer on a glass substrate; (3) preparing a perovskite precursor solution, uniformly coating the prepared perovskite precursor solution on the surface of the electron transport layer to obtain a perovskite wet film, and annealing the perovskite wet film to obtain a perovskite layer; (4) preparing a passivation solution, and spin coating a passivation layer on the surface of the perovskite layer. The passivation solution is prepared by dissolving octyl ammonium acetate in isopropanol and stirring evenly. The concentration of the passivation solution is 0.01-0.03 M. (5) Brush carbon paste on the passivation layer and anneal to obtain a carbon electrode perovskite solar cell.

2. The method for preparing a high-efficiency carbon-based hole-free perovskite solar cell according to claim 1, characterized in that: When cleaning the glass substrate, use anhydrous ethanol, daily detergent, deionized water, isopropyl alcohol and anhydrous ethanol to ultrasonically clean the glass substrate for 15 to 20 minutes respectively, then dry it at 50 to 60°C for 10 to 15 minutes, and then use ultraviolet ozone (UV) treatment for 10 to 20 minutes.

3. The method for preparing a high-efficiency carbon-based hole-free perovskite solar cell according to claim 1, characterized in that: In the step (3), the perovskite wet film is applied by spin coating.

4. The method for preparing a high-efficiency carbon-based hole-free perovskite solar cell according to claim 1, characterized in that: The calcium carbonate precursor solution is prepared by dissolving lead iodide and methylammonium iodide in an organic solvent and stirring the solution for 5 to 8 hours. The molar concentration of lead iodide is 2 to 2.3 mol / L, the molar concentration of methylammonium iodide is 2 to 2.3 mol / L, and the organic solvent is a mixed solvent of dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) in a volume ratio of 4:1 to 9:

1.

5. The method for preparing a high-efficiency carbon-based hole-free perovskite solar cell according to claim 1, characterized in that: Each 1.2×1.2 cm 2 40~60 μL of passivation agent solution was coated on the perovskite layer, and the coating machine was started. The spin coating speed was 4000 rpm and the spin coating time was 30 s. After the spin coating, the passivation layer was obtained by heating at 100°C for 5~10 min.

6. The method for preparing a high-efficiency carbon-based hole-free perovskite solar cell according to claim 1, characterized in that: The spin-coated electron transport layer is prepared by mixing a 15 wt% tin dioxide aqueous dispersion and deionized water in a volume ratio of 1:4 to obtain a tin oxide solution, and applying the tin oxide solution by spin coating on each 1.2×1.2 cm 2 45 ul of tin oxide solution was spin-coated on a glass substrate, and the coating machine was started. The coating speed was 4000 rpm and the coating time was 30 s. After the coating was completed, the electron transport layer was heated at 150 °C for 30 min to obtain the electron transport layer.

7. The method for preparing a high-efficiency carbon-based hole-free perovskite solar cell according to claim 1, characterized in that: The coated perovskite precursor solution is prepared by filtering the stirred perovskite precursor solution with a disposable sterile syringe with a polytetrafluoroethylene organic filter membrane, and then coating the solution evenly on the electron transport layer, with a thickness of 1×1 cm 2 40 μL of perovskite precursor solution was coated on the electron transport layer, and the coating machine was started. The spin coating speed was 3000 rpm and the spin coating time was 30 s. At the 15th s of spin coating, 300 μL of anti-solvent ethyl acetate was added.

8. The method for preparing a high-efficiency carbon-based hole-free perovskite solar cell according to claim 1, characterized in that: In the step (3), the perovskite wet film is annealed by heating at 130° C. for 10 to 15 minutes to obtain the perovskite layer.

9. The method for preparing a high-efficiency carbon-based hole-free perovskite solar cell according to claim 1, characterized in that: The coating process and annealing process of the titanium ore layer are both carried out in an air environment with a humidity requirement of 40-50%.

10. The method for preparing a high-efficiency carbon-based hole-free perovskite solar cell according to claim 1, characterized in that: The carbon paste in step (5) is a conductive carbon paste, and the conductive carbon paste is printed on the surface of the passivation layer by screen printing, and heated at 120° C. for 15 min to obtain a carbon electrode perovskite solar cell.

Citation Information

Patent Citations

  • Perovskite solar cell capable of being rapidly annealed in air and preparation method of perovskite solar cell

    CN113903861A

  • Inverse perovskite solar cell and preparation method thereof

    CN116669444A

  • Method for reducing surface leakage current of perovskite single crystal, perovskite single crystal and detector

    CN117984163A

  • Carbon-based perovskite solar cell based on interface passivation layer

    CN118890912A

  • Flexible Perovskite Solar Cells and Fabrication thereof

    US20240407183A1

Cited By

  • Omnibearing annealing preparation method of perovskite thin film, perovskite thin film and application of perovskite thin film

    CN120112146A